Modified bowel preparation regimen for use in second‐generation colon capsule endoscopy in patients with ulcerative colitis. Issue 5 (26th March 2014) - Usui, Shingo; Hosoe, Naoki; Matsuoka, Katsuyoshi; Kobayashi, Taku; Nakano, Masaru; Naganuma, Makoto; Ishibashi, Yuka; Kimura, Kayoko; Yoneno, Kazuaki; Kashiwagi, Kazuhiro; Hisamatsu, Tadakazu; Inoue, Nagamu; et al.
<x xml:space="preserve">Abstract</x> Background and Aim We have reported that second‐generation colon capsule endoscopy (CCE‐2) might be feasible for assessing the severity of mucosal inflammation in ulcerative colitis (UC). However, because of the low rate (69%) of complete evaluation of the colon and owing to inadequate cleansing. We believe that the method of bowel preparation could be improved by reducing volume. In the present study, we attempted to improve the colon‐cleansing regimen in order to optimize the usefulness of CCE‐2 in the management of UC patients. Methods Twenty patients with histologically confirmed UC were enrolled. Patients took a maximum 2.2 L lavage solution (polyethylene glycol solution and magnesium citrate) in two or three divided doses. To assess the effectiveness of the modified bowel preparation regimen, we evaluated the rate of total colonobservation, the effectiveness of bowel cleansing, andinterobserver agreement in assessing UC disease activity. We used a four‐point grading scale (poor, fair, good, and excellent) for evaluating the quality of bowel cleansing. Matts' endoscopic score was used to evaluate disease activity. Results The rate of total colon observation was 85%, and 15 patients (75%) excreted the CCE‐2 within 8 h. The proportion of excellent plus good cleansing was approximately 60%. There was a substantial interobserver agreement (κ = 0.777) in assessment of overall cleansing, which was still substantial at the fair cleansing level (κ = 0.700). Conclusion Using CCE‐2, the modified bowel preparation regimen, with reduced volume has the potential to succeed in the evaluation of mucosal severity in UC.